Polyneuropathy in Acute Lymphoblastic Leukemia Long-Term Survivors: Clinical and Electrophysiological Characteristics With the Impact of Radiotherapy - Kroczka, Slawomir; Stepien, Konrad; Witek-Motyl, Izabela; Klekawka, Tomasz; Kapusta, Eryk; Biedron, Agnieszka; Skorek, Pawel; Twardowska, Hanna; Stasik, Klaudia; Skoczen, Szymon (Frontiers in Pediatrics, 2021)
Introduction: Acute lymphoblastic leukemia (ALL) is the most common childhood cancer with one of the highest survival rates. Long-term complications that occur after intensive oncological treatment often impair a normal daily functioning. However, existing data on peripheral nervous system condition in ALL survivors remain conflicting. Material and Methods: The study group consisted of 215 ALL survivors. Patients were treated with New York (NY, n=45), previous modified Berlin-Frankfurt-Münster (pBFM, n=64) and BFM95 (n=106) protocols. Time elapsed between the end of the treatment and the control examination varied from 0.3 to 20.9 years. The analyzed patients underwent a neurophysiological analysis with electroneurography (ENG) of motor (median and peroneal) and sensory (median and sural) nerves as well as electromyography (EMG) of tibialis anterior, vastus lateralis and interosseous I muscles. In order to assess the impact of radiotherapy on recorded neurophysiological responses, a joint analysis of NY and pBFM groups was performed. Results: Clinical symptoms of polyneuropathy were noted among 102 (47.4%) children during the ALL therapy and in 111 (51.6%) during follow-up. Polyneuropathy at the time of treatment was diagnosed in 57.8% participants from NY group, 35.9% - pBFM and 50.0% - BFM95 (P=0.145). The significantly highest incidence of polyneuropathy during the control was observed in NY group (68.9%, P<0.001 vs pBFM, P=0.002 vs BFM95). The most common abnormalities within all the protocols were demyelination (NY: 44.4%, pBFM: 59.4%, BFM95: 41.5%), in contrast to the least frequently registered isolated axonal changes. The negative impact of oncological treatment on neurophysiological parameters in ALL survivors was observed. Complex disorders in motor nerve, sensory nerve and motor unit potentials were registered with the dominant role of motor-sensory neuropathy in all analyzed protocols. In turn, the harmful effect of radiotherapy was clearly marked in EMG parameters. Conclusions: Detailed neurophysiological analysis in long-term childhood ALL survivors has shown generalized abnormalities in registered parameters. To our knowledge current study is the largest and one of the most comprehensive research examining disturbances in ENG and EMG in this group of patients. Moreover, as demonstrated for the first time, radiotherapy can also have a negative impact on peripheral nerve conduction parameters.